FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PUBLIK DI KANTOR KEPALA DESA KOMPE BERANGIN KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI TAHUN 2017-218 DI PROVINSI RIAU TAHUN 2018-2019 - Wirda Ningsi; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In the context of the modern state, public services have become increasingly important institutions and professions. As a profession, public services are based on principles of professionalism and ethics such as accountability, effectiveness, efficiency, integrity, neutrality, and fairness for all recipientsof. Undang-Undang Nomor 23 tahun 2014 tentang pemerintah daerah, the welfare of local communities, competitiveness between regions, and community participation. Weak and low quality of governance on the one hand it can be understood that the government as a public servant is still experiencing helplessness. This helplessness not only overwhelms the government at the central and regional levels but is also experienced by the government in the smallest level village. More specific village service affairs have been regulated in the Regulation of Menteri Dalam Negeri Nomor 2 Tahun 2017  Tentang Standar Pelayanan Minimal Desa (SPMDes). SPMDes Aims to: Encourage the acceleration of services to the community, Provide services, As a tool of community control over the performance of government desa. The formulation of the problem in this study is how the quality of public services kompe berangin village of Cerenti Subdistrict of Kuantan Singingi district and what are the factors that affect the quality of public services. The purpose of this study was to identify the quality of public services in the office of the head of Kompe Berangin village in Cerenti district of Kuantan Singingi, and to identify factors that affect the quality of public services in kompe berangin village of Cerenti subdistrict of Kuantan Singing district. This research refers to the characteristics or attributes that contribute to determining the quality of public services from Tjiptono. Research method used is descriptive method with qualitative approach.According to the analysis of the authors of the study showed that the quality of public services in kompe Berangin village of Cerenti subdistrit of Kuantan Singingi district is still low, because there are still problems regarding how the public service process itself. The attributes of supporting the service have not been carried out properly, the inaccuracy of time in the process of service and village officials who are often not in the village office. Village officials increase the attitude of commitment and consistent in the implementation of public services so that the public service process runs well, and also the village government Kompe Berangin improve the quality of service quality with adequate facilities and infrastructure.Keywords: Public Service, Professionalism, Akuntabilitas, Efficiency .